Persepsi Nasabah Tentang Implementasi Shariah Compliance dan Good Corporate Governance Terhadap Loyalitas Nasabah BRI Syariah Kantor Cabang Sidoarjo - Ibrahim, Mohammad Iqbal; Rachmawati, Lucky (Jurnal Ekonomika dan Bisnis Islam, 2020)
Abstract The purpose of this research aims to determine whether the shariah compliance (X1) and good corporate governance (X2) affect the loyalty of customers of (Y) bank BRI Syariah Kantor Cabang Sidoarjo. The sample used in this research were 80 respondent from the customers of bank BRI Syariah Kantor Cabang Sidoarjo. The data collection method used in this study was by distributing questionnaires or numbers via online Google Form to the customers of bank BRI Syariah Kantor Cabang Sidoarjo who has any product at there. This research used  the Instrumen Test, Multiple Regression Analysis Test, and Hypothesis Test. The results of this study indicate that shariah compliance has a positive effect on loyalty of the customers. In addition, good corporate governance also influences positively and significantly on the loyalty of the customers. Shariah Compliance and Good Corporate Governance also influence 0,356 or 35,6% to loyality of the customers Bank BRI Syariah KC Sidoarjo and also 64,4% were influenced by another factor.